Ceramic compositions for heat exchangers and construction methods using the same
Patent Information
- Application Number
- KR1020240125527
- Authority / Receiving Office
- KR · KR
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2024-09-13
- Publication Date
- 2026-09-18
- Estimated Expiration
- 2044-09-13
Smart Images

Figure 112024101185512-PAT00025_ABST
Abstract
Description
Technology Field
[0001] The present invention relates to a ceramic composition for a heat exchanger and a construction method using the same, and more particularly to a ceramic composition for a heat exchanger of a waste heat recovery system and a construction method using the same. Background Technology
[0002] Waste heat recovery systems are widely utilized in various industries, including chemical, steel, wood, paper, and food manufacturing, playing a crucial role in improving energy efficiency by recovering waste heat generated during industrial processes. These systems reduce energy consumption and cut costs by recovering waste heat from sources such as combustion gases, cooling tower exhaust air, and process gases, and utilizing it either for the process itself or for other purposes like heating.
[0003] Heat exchangers, a key component of waste heat recovery systems, serve as devices for recovering waste heat, and their performance and durability are directly linked to the overall efficiency of the system. In particular, to address the low-temperature corrosion issues that occur during low-temperature waste heat recovery, materials with excellent corrosion resistance must be used in heat exchangers. While metal heat exchangers have traditionally been used, various compositions are currently being developed to prevent metal corrosion and improve heat transfer performance. These heat exchanger compositions maintain corrosion resistance not only in low-temperature environments but also in high-temperature environments, enabling economically efficient heat exchange. These ceramic compositions are lightweight, easy to process, and more resistant to corrosion than metals, making them effective in solving low-temperature corrosion problems. The chemical properties and thermal stability of ceramic compositions determine the long-term performance of the waste heat recovery system and play a crucial role in reducing system maintenance costs and increasing energy recovery efficiency.
[0004] However, in the waste heat recovery process, particularly for low-temperature waste heat (approximately 150°C or lower), low-temperature corrosion occurring during the recovery poses a problem. Low-temperature corrosion accelerates metal corrosion as moisture condensed on the heat exchanger surface combines with compounds in the exhaust gas, leading to a reduced lifespan and increased maintenance costs. Consequently, low-temperature waste heat was often not recovered, or the recovered amount was insufficient.
[0005] Conversely, for high-temperature waste heat (200°C or higher), waste heat recovery devices using expensive materials with excellent acid and corrosion resistance are utilized because the amount of heat that can be recovered is large and the economic benefits are significant. Although the initial investment cost for such high-temperature devices is high, costs can be reduced in the long run by effectively recovering high-temperature waste heat. However, for low-temperature waste heat below 200°C, the amount of heat is small, so the economic feasibility of devices to recover it is low, and thus low-temperature waste heat recovery is practically not carried out or is limited. The problem to be solved
[0006] The present invention provides a coating agent and a method for applying the same, which is applied to the metal heat transfer surface of a heat exchanger included in a waste heat recovery device to provide excellent durability and corrosion resistance even in high-temperature environments and prevent low-temperature corrosion. means of solving the problem
[0007] A ceramic composition for a heat exchanger of a waste heat recovery system according to the present invention is formed by adding a dispersant, a thickener, a curing agent, and a crack-preventing agent to an inorganic binder to form a ceramic coating agent, wherein the inorganic binder comprises 45-60% by weight of silica sol, 10-18% by weight of liquid sodium silicate (Na2SiO₃), 10-18% by weight of liquid potassium silicate (K2SiO₃), and 5-9% by weight of liquid lithium silicate (Li2SiO₃), and based on 100% by weight of the inorganic binder, 0.1-5 parts by weight of dispersant, 0.5-3 parts by weight of thickener, 1-10 parts by weight of curing agent, and 1-5 parts by weight of crack-preventing agent are added.
[0008] In addition, the above dispersant may include at least one of polysorbate, polycarboxylate, and polyphosphate.
[0009] In addition, the above thickener may include at least one of hydroxyethyl cellulose (HEC), carboxymethyl cellulose (CMC), and silica powder.
[0010] In addition, the curing agent may include at least one of polyamide, isocyanate, and aluminum silicate.
[0011] In addition, the crack-preventing agent may include at least one of silicone resin, rubber-based additives, and polyolefin wax.
[0012] In addition, based on 100 parts by weight of the ceramic coating agent, 5 to 15 parts by weight of acrylic resin and 3 to 10 parts by weight of zinc oxide may be added.
[0014] On the other hand, a method for applying a ceramic composition for a heat exchanger of a waste heat recovery system according to the present invention comprises the steps of: preparing a ceramic coating agent by adding 0.1 to 5 parts by weight of a dispersant, 0.5 to 3 parts by weight of a thickener, 1 to 10 parts by weight of a curing agent, and 1 to 5 parts by weight of a crack inhibitor to an inorganic binder comprising 45 to 60 wt% of silica sol, 10 to 18 wt% of liquid sodium silicate (Na2SiO₃), 10 to 18 wt% of liquid potassium silicate (K2SiO₃), and 5 to 9 wt% of liquid lithium silicate (Li2SiO₃), based on 100 parts by weight of the inorganic binder; and adding 5 to 15 parts by weight of acrylic resin and 3 to 10 parts by weight of zinc oxide, based on 100 parts by weight of the ceramic coating agent. The method includes the step of applying a ceramic coating agent to an application surface within a heat exchanger of a waste heat recovery device, wherein the above preparation is added; and the step of heat-curing the application surface within a heat exchanger of the waste heat recovery device at a temperature of 150 to 250°C for 20 to 30 minutes.
[0015] In addition, the above heat curing can be performed in a four-way manner. Effects of the invention
[0016] The ceramic coating agent according to the present invention is applied to the metal heat transfer surface of a heat exchanger included in a waste heat recovery device, providing excellent durability and corrosion resistance even in high-temperature environments, and preventing low-temperature corrosion, thereby enabling waste heat recovery down to a temperature 30°C lower. Brief explanation of the drawing
[0017] FIG. 1 is a flowchart illustrating a method for constructing a ceramic composition for a heat exchanger of a waste heat recovery system according to one embodiment of the present invention. Specific details for implementing the invention
[0018] Embodiments of the present invention will be described below with reference to the attached drawings. Unless otherwise specifically defined or mentioned, terms indicating direction used in this description are based on the state shown in the drawings. Additionally, throughout each embodiment, the same reference numeral indicates the same component. Meanwhile, the thickness or dimensions of each component shown in the drawings may be exaggerated for convenience of explanation and do not imply that it must actually be constructed according to the corresponding dimensions or ratios between components.
[0020] The present invention relates to a technology for manufacturing a ceramic coating agent by mixing a dispersant, a thickener, a curing agent, and a crack-preventing agent with an inorganic binder having silica sol, liquid sodium silicate, liquid potassium silicate, and liquid lithium silicate as main components. A ceramic coating agent according to one embodiment of the present invention is applied to the metal heat transfer surface of a heat exchanger included in a waste heat recovery device, providing excellent durability and corrosion resistance even in high-temperature environments, and preventing low-temperature corrosion, thereby enabling waste heat recovery even at low temperatures.
[0021] The following explains in detail.
[0023] The ceramic coating agent is formed by mixing a dispersant, a thickener, a curing agent, and a crack-preventing agent with an inorganic binder. The inorganic binder comprises 45-60 wt% silica sol, 10-18 wt% liquid sodium silicate (Na2SiO₃), 10-18 wt% liquid potassium silicate (K2SiO₃), and 5-9 wt% liquid lithium silicate (Li2SiO₃), and is formed by adding a dispersant, a thickener, a curing agent, and a crack-preventing agent thereto.
[0024] Here, based on 100 parts by weight of inorganic binder, a dispersant is added in an amount of 0.1 to 5 parts by weight, a thickener is added in an amount of 0.5 to 3 parts by weight, a curing agent is added in an amount of 1 to 10 parts by weight, and a crack inhibitor is added in an amount of 1 to 5 parts by weight.
[0025] In addition, additives such as acrylic resin and zinc oxide are added to compensate for the brittleness of the ceramic film, and by controlling the thermal expansion rate of the coating material to maintain a rate similar to that of a metal heat transfer surface, cracking and peeling of the coating surface are prevented. This performance can be enhanced by adding appropriate additives depending on the type of surface to be treated prior to application.
[0027] Silica sol acts as an inorganic binder and plays a crucial role in the hardness and durability of the coating film. The silica sol content is typically 45 to 60 weight percent. If the silica sol content exceeds 60%, the film becomes excessively hard, failing to absorb the difference in thermal expansion with the metal heat transfer surface, which increases the likelihood of cracking. Additionally, a reduction in the proportion of other components may lead to a decrease in the film's water resistance and chemical resistance. If the silica sol content is less than 40%, the film lacks sufficient hardness and durability, becoming vulnerable to high-temperature environments, external impacts, and thermal shock, and the film may wear out easily. In other words, within the appropriate silica sol content range, a balance between the film's hardness and flexibility is maintained, effectively absorbing the difference in thermal expansion and ensuring the film remains crack-free even at high temperatures.
[0028] Liquid sodium silicate (Sodium Silicate, Na Sodium silicate plays a role in improving the adhesion and chemical resistance of the coating film. The sodium silicate content is included in the range of 10 to 18 weight percent. If the sodium silicate content exceeds 18%, the coating film becomes excessively alkaline, increasing the likelihood of excessive reaction with the metal surface or corrosion. At high temperatures, corrosiveness may become stronger than chemical resistance. If the sodium silicate content is less than 10%, the adhesion of the coating film is insufficient, making it less likely to adhere properly to the metal surface and easily peel off, while durability is reduced. In other words, at an appropriate sodium silicate content (10–18%), it provides strong adhesion to the metal surface to form a stable coating film and maintains chemical and heat resistance even at high temperatures.
[0029] Liquid potassium silicate (K2SiO₃) improves the water resistance of the coating film and helps maintain stable performance even at high temperatures. The potassium silicate content is included in the range of 10 to 18 weight percent.
[0030] If the potassium silicate content exceeds 18%, the water resistance of the coating film may increase, but its hardness decreases, making it vulnerable to external impacts, and the uniformity of the film may deteriorate during the curing process. If the potassium silicate content is less than 10%, the water and chemical resistance of the coating film decrease, which may lead to reduced performance in high-temperature or humid environments, and the likelihood of damage or corrosion increases when the film is exposed to moisture. In other words, when the potassium silicate content is within the appropriate range (10–18%), the water and chemical resistance of the coating film are enhanced, providing stable performance without cracking even in high-temperature and high-humidity environments.
[0031] Liquid lithium silicate (Li2SiO₃) plays a role in improving the chemical resistance and corrosion resistance of the coating film, and the optimal content is set to 5–9 wt%. If the lithium silicate content exceeds 9%, the hardness and chemical resistance of the coating film can be maximized; however, due to excessive curing, the film becomes hard and loses flexibility, increasing the likelihood of cracking. In particular, the risk of the coating film peeling off increases due to the difference in thermal expansion rates with the metal in high-temperature environments. If the lithium silicate content is less than 5%, the chemical resistance and corrosion resistance of the coating film deteriorate in high-temperature environments, making the metal surface susceptible to corrosion. In other words, at the optimal lithium silicate content (5–9%), the chemical resistance and corrosion resistance of the coating film are maintained even at high temperatures, and the difference in thermal expansion rates with the metal surface is minimized to form a crack-free coating film.
[0034] The table below specifically lists the examples and comparative examples according to the ratio of each component of the mineral binder. It was prepared along with items for measuring differences in effectiveness to allow for a comparison of the differences based on each component ratio.
[0036] Dispersants are additives that help ensure the uniform distribution of the components of ceramic coatings. By allowing particles to disperse evenly within the coating material, they enhance the uniformity and stability of the coating.
[0037] The dispersant may include at least one of polysorbate, polycarboxylate, and polyphosphate.
[0038] The dispersant is added in an amount of 0.1 to 5 parts by weight based on 100 parts by weight of the inorganic binder, and within this range, it is determined in proportion to the particle size and concentration. If the amount of dispersant is insufficient, the particles are not mixed uniformly, resulting in reduced uniformity of the coating film, whereas if it is too much, the coating performance may be degraded.
[0039] Thickeners improve workability by controlling the viscosity of the coating agent and help maintain a uniform thickness of the film during coating. The thickener may include at least one of hydroxyethyl cellulose (HEC), carboxymethyl cellulose (CMC), and silica powder.
[0040] The thickener is added in an amount of 0.5 to 3 parts by weight based on 100 parts by weight of the inorganic binder. The use of an appropriate thickener within this range allows the coating thickness to be maintained uniformly.
[0041] A curing agent promotes a chemical reaction when the coating material is cured at high temperatures, causing the coating film to harden. The selection of the curing agent depends on the properties of the coating material, and it is often activated by heat. The curing agent may include at least one of polyamide, isocyanate, and aluminum silicate.
[0042] The curing agent is added in an amount of 1 to 10 parts by weight based on 100 parts by weight of the inorganic binder. The amount of curing agent affects the curing speed of the coating material and the physical properties after curing.
[0043] Crack inhibitors serve to prevent cracks that occur when a coating film undergoes thermal expansion or contraction at high temperatures. These additives impart flexibility to the coating film, thereby reducing crack formation. Crack inhibitors may include at least one of silicone resin, rubber-based additives, and polyolefin wax.
[0044] The crack inhibitor is added in an amount of 1 to 5 parts by weight based on 100 parts by weight of the inorganic binder. The crack inhibitor optimizes crack prevention in accordance with the thermal expansion and contraction of the coating layer. If the crack inhibitor is not used properly, the coating film may crack at high temperatures.
[0045] These additives play a crucial role in optimizing the performance of the ceramic coating layer through their respective functions. The selection and ratio of each additive vary depending on the purpose of the coating and the usage environment, and optimal coating performance can be secured by maintaining appropriate ratios.
[0047] In the present invention, a ceramic coating agent is applied to the heat transfer surface of a heat exchanger made of low-cost materials such as aluminum, carbon steel, SUS304, and copper, and water resistance, acid resistance, and corrosion resistance are enhanced through thermal curing. Thermal curing is performed at a temperature of 150 to 250°C for 20 minutes or more, and during this process, a film of the coating material is formed, and the durability of the heat exchanger is improved.
[0048] At this time, additives such as acrylic resin and zinc oxide are added to compensate for the brittleness of the ceramic film, and by controlling the thermal expansion rate of the coating material to maintain it similar to that of the metal heat transfer surface, cracking and peeling of the coating surface are prevented. Through this, damage to the metal heat transfer surface can be minimized, and the efficiency of the heat exchanger can be increased. Based on 100 parts by weight of the ceramic coating agent described above, 5 to 15 parts by weight of acrylic resin and 3 to 10 parts by weight of zinc oxide are added and used.
[0050] The method of using additives such as acrylic resin and zinc oxide to compensate for the brittleness of ceramic coatings is as follows. Acrylic resin provides flexibility to the ceramic coating film, thereby compensating for brittleness. Adding acrylic resin to the ceramic coating in an appropriate ratio can prevent cracking and peeling caused by thermal expansion.
[0051] The acrylic resin content may vary depending on the purpose of the coating and the application environment; if the amount is too high, the strength of the coating film may be weakened, while if it is too low, it is difficult to obtain the desired effect from the addition.
[0052] Acrylic resin is mixed directly into other components of the coating agent (primarily inorganic binders) in liquid form. During the mixing process, a high-speed stirrer is used to ensure uniform mixing. If not mixed sufficiently, the uniformity and performance of the coating film may be compromised.
[0053] Acrylic resin is cured by heat, and thermal curing is carried out at 150–250°C together with a ceramic coating agent. During the thermal curing process, the acrylic resin plays a role in maintaining the strength of the coating film while maintaining flexibility.
[0054] Zinc oxide is an important additive that complements the physical properties of ceramic coatings and controls their expansion rate. To match the thermal expansion rate of the ceramic coating to that of a metal heat transfer surface, zinc oxide is added in an appropriate amount to minimize the difference in expansion.
[0055] The zinc oxide content ratio is adjusted according to the thermal expansion coefficient of the metal to be applied. Excessive addition of zinc oxide can degrade the physical properties of the coating film, while too little makes it difficult to achieve the intended effect.
[0056] Zinc oxide is used in the form of a fine powder and is mixed with other inorganic binders and acrylic resin. During this process, a dispersant ensures that the zinc oxide particles are uniformly distributed. Sufficient stirring is required during mixing, as uneven dispersion increases the likelihood of cracking in the coating film. Zinc oxide is chemically stabilized along with the acrylic resin during the heat-curing process and plays a role in appropriately controlling the thermal expansion rate of the coating film.
[0057] In this way, acrylic resin and zinc oxide act complementarily in ceramic coatings to compensate for the brittleness of the coating film and contribute to solving the problem of thermal expansion.
[0058] In addition to acrylic resin and zinc oxide, the coating layer may include other additives such as the following that help form a thermal expansion coefficient similar to that of the metal heat transfer surface. These additives adjust the physical properties and thermal expansion coefficient of the coating material and contribute to preventing cracking and peeling of the coating surface by minimizing the difference in thermal expansion with the metal.
[0059] Silica is a highly stable inorganic material with a low coefficient of thermal expansion, making it useful for reducing the expansion difference with metal heat transfer surfaces. Adding fine silica particles to coating materials enhances the thermal stability of the coating layer, thereby strengthening durability at high temperatures. Silica suppresses the thermal expansion of the coating layer, improves alignment with the metal heat transfer surface, and minimizes crack formation.
[0060] Titanium dioxide (TiO2) possesses strong durability and a low coefficient of thermal expansion, significantly enhancing thermal stability and durability. Furthermore, it can impart flexibility to the coating layer while providing high hardness, thereby reducing the difference in thermal expansion compared to metals. Alumina (Al2O₃) is an additive that offers excellent heat and corrosion resistance, with particularly outstanding stability at high temperatures. Alumina provides a coefficient of thermal expansion similar to that of metal heat transfer surfaces, which can reduce damage caused by thermal shock. Alumina increases the strength of the coating layer and makes its coefficient of thermal expansion similar to that of metal, ensuring stability even in high-temperature environments.
[0061] Ceramic fillers (e.g., aluminum nitride, silicon carbide, etc.) can improve the thermal properties of coating materials by providing a low coefficient of thermal expansion and high heat resistance. These fillers suppress the expansion of the coating layer and form a uniform structure, maintaining stability even at high temperatures. Ceramic fillers increase the physical strength of the coating layer while reducing the difference in thermal expansion with the metal heat transfer surface.
[0062] Magnesia (MgO) is a high-heat-resistant material used as a refractory component. MgO lowers the coefficient of thermal expansion of the coating film and prevents cracking caused by differences in thermal expansion. Magnesia provides thermal stability to the coating material and matches the coefficient of thermal expansion with that of the metal heat transfer surface.
[0063] Boron nitride (BN) has a very low coefficient of thermal expansion and provides high thermal conductivity and heat resistance. This minimizes the difference in thermal expansion, especially at high temperatures, thereby increasing compatibility with the metal heat transfer surface. Boron nitride significantly improves the durability of the coating material and prevents cracking of the coating layer by reducing the difference in thermal expansion with the metal heat transfer surface.
[0064] These additives contribute to adjusting the thermal expansion coefficient of the ceramic coating layer to be similar to that of a metal heat transfer surface, thereby providing a stable and highly durable coating even in high-temperature environments. The selection of each additive is determined by the application of the coating and the characteristics of the metal to which it is applied.
[0066]
[0067]
[0068] Table 1 shows the component ratios of the examples and comparative examples, and Table 2 shows the comparison of the examples and comparative examples in terms of each characteristic.
[0069] In terms of durability (MPa), high durability is maintained in the example where the silica sol content is appropriate, but in Comparative Example 1, durability decreases when the silica sol content is low and the liquid sodium silicate is excessive. In Comparative Example 2, durability is also somewhat reduced even when the silica sol is excessive.
[0070] In terms of thermal expansion rate (%), the example shows a thermal expansion rate similar to that of a metal heat transfer surface, but in Comparative Example 1, the expansion rate increases significantly due to an excess of liquid sodium silicate. Conversely, in Comparative Example 2, the thermal expansion rate decreases excessively due to an excess of silica sol.
[0071] In terms of heat resistance (°C), Examples 1 and 2 have excellent heat resistance in high-temperature environments, but Comparative Example 1 has poor heat resistance at high temperatures due to the low silica sol content. Comparative Example 2 also fails to secure optimal heat resistance due to an excessive amount of silica sol.
[0072] The crack prevention rate (%) depends largely on the appropriate ratio of acrylic resin and zinc oxide. In Examples 1 and 2, the crack prevention rate is high, but in Comparative Example 1, the ratio of acrylic resin to zinc oxide is low, resulting in a low crack prevention rate. In Comparative Example 2, the crack prevention rate is low because the coating film becomes excessively hard due to the excessive use of silica sol.
[0073] Regarding adhesion strength (N / m²), the adhesion strength in the examples is high due to the balanced component ratio, whereas in Comparative Example 1, the adhesion strength is reduced due to the excessive use of sodium silicate. In Comparative Example 2, the adhesion strength is somewhat reduced due to a lack of flexibility after curing caused by an excessive amount of silica sol.
[0074] In terms of water resistance (time), the example has excellent water resistance, but in Comparative Example 1, water resistance is reduced due to an excess of sodium silicate, and in Comparative Example 2, water resistance is lower due to a lack of lithium silicate.
[0075] In other words, the example exhibits excellent performance in terms of durability, thermal expansion rate, heat resistance, and crack prevention rate due to a balanced component ratio. On the other hand, Comparative Example 1 shows poor overall performance due to a lack of silica sol and an excess of sodium silicate. In Comparative Example 2, the excessive use of silica sol results in insufficient flexibility of the coating film after curing, leading to a decrease in crack prevention rate and adhesion.
[0076] As a result, it can be confirmed that the example exhibits more balanced performance and that optimizing the ratio of each component is important.
[0078] The construction method according to the present invention applies a ceramic coating agent to the heat transfer surface of a heat exchanger made of low-cost materials such as aluminum, carbon steel, SUS304, and copper, and after applying a formulation according to the surface to be applied, enhances water resistance, acid resistance, and corrosion resistance through thermal curing. Thermal curing is performed at a temperature of 150 to 250°C for 20 to 30 minutes, and during this process, a film of the coating material is formed and the durability of the heat exchanger is improved.
[0079] When applying ceramic coatings, if the heat curing process takes too long, the physical and chemical properties of the coating may change. Although the curing time can be up to 60 minutes at a temperature of 150 to 250°C, if more time passes, the coating film may become too hard and lose its flexibility. This prevents the coating film from responding to thermal expansion or contraction, increasing the likelihood of cracking or peeling.
[0080] In addition, regarding material degradation, in the case of acrylic resins or other organic materials, if the heat curing time is too long, they may chemically decompose or deteriorate. This can have a negative effect on the strength and durability of the coating film. Therefore, it is desirable to set the maximum limit of the heat curing time to about 60 minutes, and it is not desirable to cure for a longer period than necessary.
[0081] Furthermore, the desirable thermal curing time is approximately 20 to 30 minutes. This time range is the optimal duration for sufficient thermal curing to fully harden the coating film while preventing the loss of flexibility caused by excessive curing. Within this time frame for complete curing, the film hardens evenly and acquires stable physical properties both on the surface and within. If sufficient curing occurs during this time, the physical strength and durability of the coating film are optimized. In other words, the flexibility-providing components, such as acrylic resin, are properly cured to maintain the flexibility of the coating film, and the thermal expansion coefficients of the ceramic coating agent and the metal substrate are appropriately matched, thereby minimizing damage to the coating surface caused by thermal stress.
[0082] In conclusion, a heat curing time of 20 to 30 minutes is most desirable for optimizing the physical performance and durability of the ceramic coating film, and can be extended up to 60 minutes if necessary, but curing beyond this may degrade the physical properties of the film.
[0083] To effectively perform heat curing, hot air is generated using a direct-fired or electric hot air blower and introduced into the inlet of the heat exchanger. In the case of a direct-fired hot air blower, fuel consumption can be minimized by recovering the hot air generated from the blower, mixing it with pure oxygen or enriched oxygen, and reintroducing it into the blower inlet. In the case of an electric hot air blower, fuel consumption is reduced by recovering the hot air and reintroducing it into the blower inlet.
[0084] In addition, a four-way valve system is applied to control the flow of hot air, allowing the direction of the hot air flow to be reversed at regular intervals. This ensures that thermal curing proceeds uniformly within the heat exchanger, thereby significantly improving the performance of the heat exchanger and the durability of the coating.
[0085] The four-way valve method is one of the air flow control technologies used in heat exchangers or dryers, which involves periodically changing the direction of the air (or hot air) flow. This method ensures uniform heat exchange within the heat exchanger, thereby increasing efficiency, reducing the heat load in specific areas, and improving the quality of the heat curing or drying process.
[0086] The four-way valve system reverses the direction of airflow at the inlet and outlet of the heat exchanger at regular intervals, ensuring that heat is evenly distributed rather than concentrated in specific parts of the heat exchanger. Specifically, as hot air or air flows from the inlet to the outlet of the heat exchanger for a certain period, the temperature of the air changes due to the heat transfer surfaces within the heat exchanger, and heat is exchanged. After a certain period, the airflow is reversed. That is, the place that was previously the outlet becomes the inlet, and the place that was previously the inlet becomes the outlet, causing the air to flow in the opposite direction.
[0087] The switching of this airflow is periodically controlled by an automated valve system. The switching cycle is typically set to match the heat hardening or drying requirements of the heat exchanger, and this cycle allows for even heat exchange within.
[0088] If air flows continuously in only one direction, heat can be concentrated in specific parts of the heat exchanger. However, in the four-way valve system, heat is evenly distributed through periodic reverse flow, allowing for uniform heat exchange throughout the entire heat exchanger. This prevents non-uniformity in the heat curing or drying process and enables uniform heat treatment on the heat transfer surface.
[0090] Although preferred embodiments of the present invention have been described above, the technical concept of the present invention is not limited to the preferred embodiments described above and can be implemented in various ways within the scope that does not depart from the technical concept of the present invention as embodied in the claims.
Claims
Claim 1 A ceramic coating agent is formed by adding a dispersant, a thickener, a curing agent, and a crack-preventing agent to an inorganic binder, wherein the inorganic binder comprises 45 to 60 weight% of silica sol and liquid sodium silicate (Na₂S). ₂ SiO ₃ ) 10~18 wt%, liquid potassium silicate (Potassium Silicate, K ₂ SiO ₃ ) 10~18 wt%, liquid lithium silicate (Lithium Silicate, Li ₂ SiO ₃ A ceramic composition for a heat exchanger of a waste heat recovery system comprising 5~9% by weight, and based on 100% by weight of an inorganic binder, 0.1~5 parts by weight of a dispersant, 0.5~3 parts by weight of a thickener, 1~10 parts by weight of a curing agent, and 1~5 parts by weight of a crack inhibitor, and based on 100% by weight of the ceramic coating agent, 5~15 parts by weight of an acrylic resin and 3~10 parts by weight of zinc oxide are added. Claim 2 A ceramic composition for a heat exchanger of a waste heat recovery system, wherein the dispersant comprises at least one of polysorbate, polycarboxylate, and polyphosphate. Claim 3 A ceramic composition for a heat exchanger of a waste heat recovery system according to claim 1, wherein the thickener comprises at least one of hydroxyethyl cellulose (HEC), carboxymethyl cellulose (CMC), and silica powder. Claim 4 A ceramic composition for a heat exchanger of a waste heat recovery system according to claim 1, wherein the curing agent comprises at least one of polyamide, isocyanate, and aluminum silicate. Claim 5 In claim 1, the crack inhibitor is a ceramic composition for a heat exchanger of a waste heat recovery system comprising at least one of silicone resin, rubber-based additives, and polyolefin wax. Claim 6 delete Claim 7 45~60 wt% silica sol, liquid sodium silicate (Na ₂ SiO ₃ ) 10~18 wt%, liquid potassium silicate (Potassium Silicate, K ₂ SiO ₃ ) 10~18 wt%, liquid lithium silicate (Lithium Silicate, Li ₂ SiO ₃ A method for constructing a ceramic composition for a heat exchanger of a waste heat recovery system, comprising: a step of preparing a ceramic coating agent by adding 0.1 to 5 parts by weight of a dispersant, 0.5 to 3 parts by weight of a thickener, 1 to 10 parts by weight of a curing agent, and 1 to 5 parts by weight of a crack inhibitor to an inorganic binder containing 5 to 9 weight%, based on 100 parts by weight of the inorganic binder; a step of adding 5 to 15 parts by weight of an acrylic resin and 3 to 10 parts by weight of zinc oxide based on 100 parts by weight of the ceramic coating agent; a step of applying the ceramic coating agent with the added additives to an application surface within a heat exchanger of a waste heat recovery device; and a step of heat-curing the application surface within the heat exchanger of the waste heat recovery device at a temperature of 150 to 250°C for 20 to 30 minutes. Claim 8 In claim 7, the above-mentioned heat curing is a method for constructing a ceramic composition for a heat exchanger of a waste heat recovery system, performed in a four-way manner.
Citation Information
Patent Citations
Thermal insulation nano coating and preparation method thereof
CN117025008A
Substrate treating agent for aluminum fin material
JP2011042842A
Expandable nonorganic composition
KR1019950006071B1
The inorganic aqueous binder and paints and the makingmethod thereof
KR1020070105581A
Composition of inorganic refractory coating with heat dissipation and heat resistance, and its manufacturing method
KR1020220155546A
